The National Bilingualism Plan (PNB) and the Challenge of Internationalization in Colombia: Background and Perspectives - María Emilia Aponte Mantilla (Universidad de La Sabana, 2024)
This article intends to analyze the interdependence between the National Bilingualism Plan of Colombia and the challenge of internationalization of higher education in the country, as public policies that aim to improve the quality of education at different levels. The first focuses on strengthening the teaching of foreign languages in primary, basic, and secondary education; the latter, in higher education with the promotion of regional and global agreements for the recognition of studies, titles, and diplomas to promote access to greater academic and cultural opportunities for students, which would contribute to the economic development and the insertion of the country in the global context in a competitive manner. It aims to understand the challenge of internationalization and its deep connection with economic globalization and to establish its link with the teaching of foreign languages and the promotion of bilingualism. The National Bilingualism Plan and the development of the learning of foreign languages in Colombia are explored, and then the disconnection between both programs as a possible cause of the truncated development of bilingualism in the country is analyzed.